2021
DOI: 10.1515/secm-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for drilling process of metal-composite aeronautical structures

Abstract: Metal-composite laminates and joints are applied in aircraft manufacturing and maintenance (repairing) using aluminum alloys (AA) and glass fiber-reinforced polymer (GFRP). In these applications, drilling has a prominent place due to its vast application in aeronautical structures’ mechanical joints. Thus, this study presents the influence of uncoated carbide drills (85C, 86C, H10N), cutting speeds (v c = 20, 40, and 60 m min−1), and feed rates (f = 0.05, 0.15, and 0.25 mm rev−1) on delaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Initial studies approached the drilling of metal-composite stack 31 and CFRP 44 . While Devitte et al 31 studied the optimization of the drilling process, Hoffmann et al 44 evaluated the influence of VCCA on the quality of drilled holes. A study of the temperature in the drilling process was performed by Devitte et al 39 , which reported temperatures well below the degradation temperature for the tested conditions, with an analysis of SEM images indicating the absence of fiber deformation and matrix degradation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies approached the drilling of metal-composite stack 31 and CFRP 44 . While Devitte et al 31 studied the optimization of the drilling process, Hoffmann et al 44 evaluated the influence of VCCA on the quality of drilled holes. A study of the temperature in the drilling process was performed by Devitte et al 39 , which reported temperatures well below the degradation temperature for the tested conditions, with an analysis of SEM images indicating the absence of fiber deformation and matrix degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were presented by Voss et al 18 , who also observed that larger clearance and rake tool angles improve the surface quality and reduce tool wear. Devitte et al 31 evaluated the influence of the cutting parameters and tool geometry in the delamination in Al-GFRP-Al hybrid stack drilling. The best results were achieved using lower v c , f, and a drill with a lower point angle, lower chisel edge, and higher rake angle.…”
Section: Introductionmentioning
confidence: 99%
“…The HSS drill bits used in this experiment was diameter of 6 mm, helix and point angle of 30 o and 118 o , respectively. The various factors, like 'v', 'f', and 'd', were taken into consideration as the input cutting variables based on the prior investigation [24,25], and their levels are shown in Table 1. According to the selection of parameters, L16 orthogonal array was most suitable design to conduct the drilling experiments and are depicted in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Both high localized temperature and thrust force are directly involved in this plastic deformation [91]. As depicted in Figure 4, two types of burrs, namely, uniform and crown, can be identified at the exit of a drilled aluminum plate, depending on workpiece material properties, drilling parameters and cutting forces [109,112]. As explained by Costa et al [113], entrance hole burrs are formed by the plastic flow of the material, while exit hole burrs are caused by the conformation of the material induced by high compression rates in the center of the hole.…”
Section: Burr Height In Aluminummentioning
confidence: 99%